Identification of Algebraic and Transcendental Numbers Using Some Elementary Functions (Research Journal, 2023)
In this paper, to identify irrational numbers while appropriately emphasizing basic functions. All rational numbers can be expressed algebraically, but not all irrational numbers. Rational, irrational, algebraic numbers and transcendental numbers are mostly concerned with irrational numbers using some elementary functions.